2006
DOI: 10.1038/sj.ijo.0803209
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and physiological effects of ingesting extracts of bitter orange, green tea and guarana at rest and during treadmill walking in overweight males

Abstract: Objective: This study examined the acute effects of ingesting a widely used commercial formula containing extracts of bitter orange, green tea and guarana (Gx) on the metabolic rate and substrate utilisation in overweight, adult males at rest (study 1) and during treadmill walking (study 2). Subjects: Two different groups of 10 sedentary males with more than 20% body fat participated in studies 1 and 2. Design: In each study, subjects participated in two experimental trials during which they were given two 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…Our results are also in line with a number of studies that have demonstrated increases in whole-body EE and fat oxidation during resting conditions following GTE supplementation [7,11,12]. However, a number of studies have reported no difference in FFA or glycerol concentrations despite changes in whole-body measures of fat oxidation [13,31,32]. In the current study, fat oxidation rates were not measured during the rest period.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also in line with a number of studies that have demonstrated increases in whole-body EE and fat oxidation during resting conditions following GTE supplementation [7,11,12]. However, a number of studies have reported no difference in FFA or glycerol concentrations despite changes in whole-body measures of fat oxidation [13,31,32]. In the current study, fat oxidation rates were not measured during the rest period.…”
Section: Discussionsupporting
confidence: 91%
“…For example, administration of ascorbic acid was more effective in counteracting oxidative stress when provided through orange juice than when supplemented as a simple water solution. 32 A few studies have shown the lipolytic activity of another component of orange juice, synephrine, 33,34 an adrenergic compound that could have adverse health effects. 35,36 Nevertheless, no difference in the amount of synephrine was found between Moro and Naveline juices.…”
Section: Discussionmentioning
confidence: 99%
“…proprietary blend failed to demonstrate any metabolic shifts in obese men at rest or during moderate walking exercise at 60% of VO 2max (Sale et al, 2006). The dose of guaraná delivered in this study was not explicitly stated, though it was less than 1262 mg.…”
Section: Guaranámentioning
confidence: 99%
“…Guaraná is primarily marketed as a thermogenic aid and as a weight-loss supplement. Guaraná has been studied as a thermogenic supplement but usually in combination with other ingredients (Bérubé-Parent et al, 2005;Haller et al, 2005;Sale et al, 2006) and rarely has it been studied in exercising humans (Sale et al, 2006).…”
Section: Guaranámentioning
confidence: 99%